Analisis Faktor Keterlambatan Pada Pembangunan Proyek X - Fahira Khairani; Supriyadi, Iwan (Journal of Applied Civil Engineering and Infrastructure Technology, 2021)
In a construction project generally has its own work schedule and activities. Project planning refers to the estimates that have been generated at the time of planning. If there is a discrepancy between the planned plan and its implementation, it can cause delays in project development. Based on the s curve, in May the progress should have reached 83.8%, but the realization in the field has only reached 59.2%, As a result, late indications might be detected in the project. It's necessary to look at the dominant reasons of project delays based on the percentage data. The purpose of this study is to reveal or find the dominant factors that affect delays and solutions for delays in the construction of Project X. Data was collected by distributing questionnaires to individuals who were directly involved with project development such as contractors, supervisory consultants, and owners. Multiple linear regression analysis was used to analyze the data using SPSS V25 software. The financial factor with parameter X28, namely late payment by the owner obtaining a β value of 0.386 has proven to be the most significant factor in the delay in the construction of Project X and the effort to overcome this delay is to provide a letter to the owner to make a cash-in plan to pay off the outstanding payment in progress.